A training system for taekwondo players with impact and linear displacement data collection - Vasquez, Sebastian (2023)
Currently, technology does not accompany Peruvian high performance Taekwondo athletes in an efficient way where there is the ability to read all the physical performance data, obtain a database of it constantly and have a system that allows practicing the slide that is often used as footwork. It should be noted that there is not much prominence of the robotic sector to be applied in sport as well as the lack of data records of specific variables that can quantify the skill of high-level taekwondo players. Therefore, the purpose of this article is to promote technological assistance to increase competitiveness in Peruvian taekwondo players and to improve their physical performance. For this purpose, a training system was implemented, which has 'dommys' (kicking shields) of the official brand 'JCALICU' conditioned with a wooden plate, load cells and piezoelectrics for the reception of kicking data. There is also a paddle that will move radially to receive the axe type kick and, for the linear displacement, a motor with chain transmission will be used. The methodology used is programming, I2C serial communication, numerical simulation and PID control. The result is a training system capable of linear displacement and of displaying the data of force, reaction time and precision of the athletes' kicks in a graphic interface.